Validitas Dan Reliabilitas Instrumen Literasi Digital Siswa Kelas XI Pada Mata Pelajaran Biologi Di SMA N 1 Pekanbaru - Siti Sofea; Ummi Kalsum; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
Digital literacy is an essential competency in 21st-century Biology learning due to the complexity of biological concepts and the increasing reliance on digital learning resources. However, validated and reliable instruments for measuring students’ digital literacy skills at the senior high school level remain limited. This study aimed to analyze the validity and reliability of a digital literacy instrument for Grade XI students in Biology learning at SMA Negeri 1 Pekanbaru. This research employed a descriptive quantitative approach involving 70 Grade XI science students from classes XI.3 and XI.8. Data were collected using a digital literacy questionnaire developed based on four indicators: internet searching, hypertextual navigation, content evaluation, and knowledge assembly. Instrument validity was tested using Pearson’s Product Moment correlation at a 5% significance level, while reliability was analyzed using Cronbach’s Alpha coefficient. The results indicated that most questionnaire items had correlation coefficients (r count) exceeding the r table value, indicating that the items were valid. Furthermore, the reliability analysis yielded Cronbach’s Alpha values of 0.79 for class XI.3 and 0.88 for class XI.8, both of which exceeded the minimum reliability threshold. These findings demonstrate that the developed digital literacy instrument meets the criteria of validity and reliability and is suitable for measuring students’ digital literacy skills in Biology learning at the senior high school level. This instrument is expected to assist teachers and researchers in obtaining accurate data on students’ digital literacy abilities and in designing more effective Biology learning strategies aligned with 21st-century educational demands.